Consensus Conference on Best Practices in Live Kidney Donation: Recommendations to Optimize Education, Access, and Care. Issue 4 (3rd February 2015) - LaPointe Rudow, D.; Hays, R.; Baliga, P.; Cohen, D. J.; Cooper, M.; Danovitch, G. M.; Dew, M. A.; Gordon, E. J.; Mandelbrot, D. A.; McGuire, S.; Milton, J.; Moore, D. R.; et al.
Abstract : Live donor kidney transplantation is the best treatment option for most patients with late‐stage chronic kidney disease; however, the rate of living kidney donation has declined in the United States. A consensus conference was held June 5–6, 2014 to identify best practices and knowledge gaps pertaining to live donor kidney transplantation and living kidney donation. Transplant professionals, patients, and other key stakeholders discussed processes for educating transplant candidates and potential living donors about living kidney donation; efficiencies in the living donor evaluation process; disparities in living donation; and financial and systemic barriers to living donation. We summarize the consensus recommendations for best practices in these educational and clinical domains, future research priorities, and possible public policy initiatives to remove barriers to living kidney donation. Abstract : This article summarizes the proceedings of the June 2014 Consensus Conference on Best Practices in Live Kidney Donation, which include recommendations for educating transplant candidates and potential living donors, improving efficiencies in the living donor evaluation process, reducing disparities in living kidney donation, and steering future research and policy priorities to remove barriers to donation.